Multiresidue determination of pesticides in honey samples by gas chromatography-mass spectrometry and application in environmental contamination - Rissato, Sandra Regina [UNESP]; Galhiane, Mario Sergio [UNESP]; de Almeida, Marcos V.; Gerenutti, Marli; Apon, Benhard M. (Elsevier B.V., 2007)
A simple and fast multiresidue method has been developed to determine 48 pesticides within the major groups of pesticides (organohalogen, organophosphorous, pyrethroids and organonitrogen) in representative samples of locally produced honey, in Bauru (State of São Paulo, Brazil) during 2003-2004. The recovery results found ranged from 76% to 95% and the limits of detection were lower than 0.01 mg/kg for gas chromatography with electron impact mass spectrometric detection in the selected ion monitoring mode (GC-MS-SIM). The results indicated that most pesticides found in the samples belonged to the organohalogen and organophosphorous groups and lower levels of residues of some organonitrogen and pyretroids were also detected. Malathion residues were detected in all the samples, in a high concentration, owing to its applications to control dengue mosquitoes in the area studied. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: pesticides residue analysis; capillary gas chromatography-mass spectrometric detection with selective ion monitoring; honey; environmental contamination